2005
DOI: 10.1080/027868290920115
|View full text |Cite
|
Sign up to set email alerts
|

Particle Dynamics in a Front-Opening Unified Pod/Load Port Unit Minienvironment in the Presence of a 300 mm Wafer in Various Positions

Abstract: This article reports airflow, particle transport, and pressure differential control of a front-opening unified pod/load port unit (FOUP/LPU) minienvironment system using both experimental and computational fluid dynamics (CFD) approaches. The stochastic tracking approach in the Discrete Phase Model of Fluent software was adopted to predict particle trajectory. The predicted velocity vectors were verified by experimental ones, which were measured by a 3D ultrasonic anemometer. Particles from the upper edge of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Although infectious pathogens do not enter human bodies by the airborne route in the physical contact transmission mode, the air transport characteristics of expiratory droplets affect their surface deposition characteristics. Many studies have shown that ventilation airflow has significant impact on the deposition of aerosols in indoor environments (e.g., Chang et al 2006;Bouilly et al 2005;Hu and Hsiao (2005); etc.). One problem with the studies by Chao and Wan (2006) and is the use of an empty room in order to focus on the effect of airflows generated by mechanical ventilation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Although infectious pathogens do not enter human bodies by the airborne route in the physical contact transmission mode, the air transport characteristics of expiratory droplets affect their surface deposition characteristics. Many studies have shown that ventilation airflow has significant impact on the deposition of aerosols in indoor environments (e.g., Chang et al 2006;Bouilly et al 2005;Hu and Hsiao (2005); etc.). One problem with the studies by Chao and Wan (2006) and is the use of an empty room in order to focus on the effect of airflows generated by mechanical ventilation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Particles with moisture in the air not only contaminate wafer itself but also have effect on wire bonding which can generate product defects (Kikyuama et al, 1991;Den et al, 2006;Lin et al, 2010;Lee et al, 2015). To prevent this kind of contamination by exposure to the air, wafers on which chip is formed are stored or moved in the enclosed carrier called front opening unified pod (FOUP) and particles or AMCs remaining on wafers may diffuse into FOUP and contaminate it (Frickinger et al, 2000;Hu et al, 2005;Hu et al, 2009). Particles or AMCs adsorb onto inside of FOUP which can contaminate other wafers and FOUPs like a "contagious disease" and therefore various researches on FOUP cleaning and purge are in progress (Hu and Tsao, 2006;Hu et al, 2007;Yoo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An air recirculation system of a raised-floor return ventilation arrangement has been employed to industrial cleanrooms and received increased attention (Hu et al, 1996;Fu et al, 2001;Hu et al, 2002aHu et al, , 2002bHu and Chuah, 2003;Hu and Wu, 2003;Hu and Hsiao, 2005;Hu and Chen, 2007;Hu et al, 2009). In such raised-floor return air system, the clean air is introduced from ceiling grilles and then extracted from the raised perforated floor.…”
Section: Introductionmentioning
confidence: 99%